El trabajo práctico. Una intervanción para la formación de profesores - García, S.; Martínez, M. C.; Mondelo Alonso, Matilde (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
In this article we raise and discuss the field of teacher training with regard to practical work. We take as a point future teaching staff on one instructuve possibility of the aforementioned pract.